Dining at continuing care retirement communities: a social interaction view - Abu Bakar, Ainul Zakiah (Kansas State University, 2013)
As the number of older adults increases so does the demand for housing and personal care needs. The continuing care retirement community is unique from other senior care facilities as it provides a continuum of housing and care that caters towards an individual’s need. Foodservice is often utilized to attract older adults into retirement facilities. Such service would give residents additional opportunities to socialize with service workers as well as other patrons of the restaurant. Yet, few studies have focused on the roles of food and dining service on resident’s satisfaction with foodservice and their quality of life. Study 1 examined the relationships between residents’ perception of individual customer orientation of service employee dimensions: technical skills, social skills, motivation, and decision-making authority, with relational benefits, satisfaction and subsequent behavioral outcomes: repurchase intention and word-of-mouth. Study 2 explored the moderating effects of resident’s activity involvement and food involvement on the relationships between rapport, dining-need satisfaction and resident’s quality of life. To achieve the objectives of these studies, 412 continuing care retirement community residents from five facilities completed a self-report questionnaire. Of these, 354 were used in study 1 and study 2. Findings of the structural equation modeling (Study 1) suggested that resident’s perception of foodservice employee’s technical skills, social skills and motivation were important determinants of confidence and social benefits that led to residents’ overall satisfaction with foodservice. Satisfied resident-consumer is likely to engage in word-of-mouth and repurchase intention. Results of hierarchical multiple regressions (Study 2) revealed that perceived rapport and resident’s dining-need satisfaction are positively related to resident’s quality of life. This study also found that activity involvement and food involvement moderated the relationships between rapport and dining-need satisfaction with quality of life respectively. That is, the more involved resident has an improved quality of life.
Keywords: Behavioral intentionsCustomer orientation of service employee; Relational benefits; Customer satisfaction; Rapport; Dining-need satisfaction; Marketing (0338)